A 5;7, 5;12 double reciprocal translocation in a normal mother and a 5;7 translocation with a recombinant chromosome 5 in her normal child. Issue 4 (August 1981) - Tabor, A; Jensen, L K; Lundsteen, C; Niebuhr, E
Abstract : A phenotypically normal mother had two apparently balanced translocations involving chromosomes 5, 7, and 12. Her karyotype was 46, XX, t(5;7) (5;12) (p14q34;p14;q21), while her daughter, who was also phenotypically normal, had inherited only one of the translocations. Her karyotype was 46, XX, -5, -7, +rec(5)t(5;7) (q34;p14)mat, +der(7)t(5;7) (q34;p14)mat. The other was lost during a meiotic crossing over, giving the daughter an apparently balanced chromosome complement.